Nyctobrya maderensis (Bethune-Baker, 1891), uma espécie nova para a fauna dos Açores (Lepidoptera: Noctuidae) - Vieira, Virgilio (2023)
ABSTRACT: Nyctobrya maderensis (Bethune-Baker, 1891) is a new species to the fauna of the Azores archipelago (Portugal). It was found in Ponta Delgada and Vila Franca do Campo, on the island of São Miguel. Some notes on the distribution and ecology of this Heterocera are also given.